Analisis kualitas pelayanan program pemeriksaan kesehatan gratis dengan metode servqual terhadap kepuasan pasien - Charissa Peresia Ango; Harsali Fransiscus Lampus; Jimmy Posangi (Holistik Jurnal Kesehatan, 2026)
Background: Human resource development in the health sector has driven the implementation of a free health screening program aimed at fostering a healthy, productive, and globally competitive Indonesian population, as mandated by the Minister of Health Decree Number HK.01.07/MENKES/33/2025. Although the Wenang Community Health Center has implemented this program, various technical and non-technical obstacles persist, potentially affecting patient satisfaction. Healthcare service quality is a crucial factor due to its direct impact on patient satisfaction. Purpose: To analyze the service quality of the free health screening program using the servqual method and to examine the relationship between service quality dimensions and patient satisfaction. Method: This study employed an observational analytic quantitative design with a cross-sectional approach. A sample of 72 respondents was selected using Slovin's formula. Data were collected via a structured questionnaire that had undergone validity and reliability testing. Data analysis included gap measurement using the Servqual method, as well as statistical analysis using the Chi-Square test (bivariate) and logistic regression (multivariate) to identify variables significantly influencing patient satisfaction. Results: The average gap scores were negative. Chi-Square analysis yielded p-values ​​< 0.05 for the variables of tangibles, reliability, responsiveness, and empathy. Logistic regression analysis showed that the empathy variable had an Exp(B) value of 23.9. Average gap scores were negative, while the Q-value was < 1. Conclusion: All dimensions of service quality are associated with patient satisfaction. However, when analyzed simultaneously in a logistic regression model, only the empathy variable demonstrated a significant influence on patient satisfaction regarding the free health check-up program. Furthermore, service quality remains suboptimal. These research findings can serve as a reference for improving healthcare service quality, particularly concerning free health check-up programs at community health centers.   Keywords: Free Health Check-Ups; Patient Satisfaction; Service Quality.